PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS BINA MARGA DAN SUMBER DAYA AIR SERTA DINAS CIPTA KARYA DAN TATA RUANG KABUPATEN KUANTAN SINGINGI - Amri Samad; Dewita Suryati Ningsih; Rendra Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the influence of Leadership and Working Environment on the Performance of employees at the Department of Highways and Water Resources As well as the Office of Human Settlements and Spatial Kuantan District. This study used 98 samples. The analytical method used is descriptive analysis method is by means of a variable test, regression test, test path analysis or path analysis. From the results of the testing that has been done, Leadership and Work Environment directly affects employee performance in the Department of Highways and Water Resources As well as the Office of Human Settlements and Spatial Singingi Kuantan District. Indirect relationship leadership variable to variable performance of employees at the Department of Highways and Water Resources As well as the Office of Human Settlements and Spatial Kuantan Singingi through work environment variable is greater than the result of a direct relationship of leadership variable to variable performance.Keywords: Leadership, Work Environment, Employee Performance.